Pendekatan Kognitif Sosial pada Pembelajaran Pendidikan Agama Islam - Nelly Marhayati; Pasmah Chandra; Monna Fransisca (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The purpose of this study is to find out about the form of social cognitive theory approach from Bandura which can be applied to the learning of Islamic Education in Schools. Based on several previous studies, the cognitive approach has widely applied to learned was the cognitive approach from Piaget. The method used in this research is qualitative research with library research approach. Based on the analysis of the literature study, the approach of the social cognitive theory that can be applied to the learning of Islamic Education learning is through observational learning or modeling which includes four processes namely the process of attentional, retention, reproduction, and motivational processes. The social-cognitive approach that can be applied to Islamic education learning is on the application; curriculum, teaching, and assessment. In addition, the application of social learning theory by means of modeling is not contrary to the teachings of Islam that encourage people to make the Prophet as a model or role model in life.